Origin of apatite-dominated rock penetrating the volcaniclastic fill of the Pleistocene Bazina maar (western Czech Republic) - Rapprich,V.; Vylita,T.; Molnar,K.; Hora,J.M.; Benko,Z.; Curda,M.; Magna,T.; Koubova,M.; Pour,O.; Hrubcova,P.; Fischer,T.J. (Journal of Geosciences, 2024)
The sequence of alkaline basaltic lavas and associated pyroclastic deposits that fill Bazina maar in western Bohemia is transected by a vein of apatite-dominated rock revealed in the S4 borehole. Aside from solid vein fill, apatite also impregnates a significant part of the drilled volcanic sequence. In the main body (depth 60.00-66.60 m), apatite occurs in two texturally distinct types: common cauliflower-type apatite (type 1) is transected by veinlets of coarser (0.2 mm long) apatite crystals (type 2). Both types have grown into open spaces suggesting precipitation from fluids rather than crystallization from melt, which is consistent with generally low trace element contents with slight enrichment in Cs, Sr, U and Pb. Relative to other local Plio-Pleistocene volcanic rocks, apatite vein-fill is shifted in 87Sr/86Sr towards more radiogenic values (0.7053-0.7054). This suggests that fluids carrying mantle-derived ions mixed with groundwater interacting with granitic country-rock, as also evidenced by the purely crustal character of noble gases trapped in apatite. Unlike the mofettes occurring along the Marianske Lazne Fault on the eastern margin of the Cheb Basin, the 4He/3He ratios from Bazina apatite do not indicate mantle noble gas contribution. According to our model, the originally Sr-P-rich fluids with low 87Sr/86Sr mixed with Cs-U-enriched groundwater circulating in country-rock granites with radiogenic 87Sr/86Sr. Therefore, present-day CO2 outgassing through mofettes related mainly to the Marianske Lazne Fault (eastern margin of the Cheb Basin) is likely independent of, and unrelated to, volcanism of the Cheb-Domazlice Graben.
Keywords: fluid-precipitated apatite; Sr-isotopes; noble gases; Pleistocene; Tachov Fault; Bazina maar